Studi Tentang Pelaksanaan Pembelajaran Penjasorkes di Sekolah Dasar Negeri 85 Lubuklinggau - Supriyadi, Muhammad (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2023)
This research aims to determine the implementation of Physical Education and Orchestra Learning at State Elementary School 85 Lubuklingggau; the implementation of physical education learning consists of several problems, namely the factors of Physical Education Teachers, Facilities and Infrastructure, and Student Motivation at School. The method used in this research is descriptive research. Sampling used a purposive sampling technique, namely representatives of school principals and physical education teachers from each of the 85 Lubuklinggau State Elementary Schools used as research samples. Data collection techniques using observation and distributing questionnaires to students at State Elementary School 85 Lubuklinggau who were selected as research samples. The research results show that motivation is reasonable. This is caused by several causes, one of which is the high enthusiasm and motivation of physical education teachers in providing physical education learning materials in class. Student motivation is also an essential factor in influencing the implementation of physical education learning in schools. Apart from that, the conclusion of the discussion above regarding modifications is reasonable. The facilities and infrastructure assessed by the class teacher as modified in Physical Education, from the assessment results, are reasonable. This is because the facilities and infrastructure at SDN 85 Lubuklinggau can still be used. In conclusion, implementing physical education learning in terms of motivation, modification, and infrastructure is in the excellent category. Keywords: motivation, physical education, infrastructure